The assessment and validation of the depression, anxiety, and stress scale (DASS-21) among frontline doctors in Pakistan during fifth wave of COVID-19 - Nadeem, Muhammad Umar; Kulich, Steve J.; Bokhari, Ijaz Hussain (Frontiers in Public Health, 2023)
Objective: The study aims to document sociodemographic features, address the symptoms and levels of depression, anxiety, and stress among frontline doctors in Pakistan, and validate depression, anxiety, stress scale (DASS-21) on the context of Pakistan. Method: A cross-sectional survey was conducted throughout the regions of Pakistan on frontline doctors to document their sociodemographic patterns and the levels of depression, anxiety, and stress while dealing with the fifth wave (Omicron-variant) of the coronavirus (SARS-CoV-2) pandemic in Pakistan (Dec. 2021-Apr. 2022). Respondents (N = 319) were recruited through a snowball sampling process. Results: Though previous literature reported declines in psychological symptoms after earlier waves of COVID-19, these DASS-21 findings show that as the pandemic has worn on, frontline doctors in Pakistan are having considerable personal symptoms of depression (72.7%), anxiety (70.2%), and stress (58.3%). In addition, they are having moderate levels of depression and stress, however, severe levels of anxiety specifically about COVID-19 pandemic. The results also revealed a positive correlation between depression and anxiety (r = 0.696, p < 0.001), depression and stress (r = 0.761, p < 0.001), and anxiety and stress (r = 0.720, p < 0.001). Conclusion: Through the application of all required statistical procedures, DASS-21 is validated in the cultural context of Pakistan among this group of frontline doctors. The findings of this study can provide new directions for the policy makers (government and hospitals’ administration) of Pakistan to focus on the mental wellbeing of the doctors and to protect them from short- or long-term disorders.